1970
DOI: 10.3126/njst.v11i0.4124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change on Rice Production: A Case of Six VDCs in Jumla District

Abstract: Rice (Oryza sativa L.) is a staple crop of Nepal and is directly associated with ample water and minimum fluctuation of temperature that could affect on its production. Jumla is the unique place where rice is cultivated in the highest altitude (3000 m) in the world. To find out changes in rice production due to climatic effect, six VDCs of Jumla were chosen for the study. Household survey, participatory rapid appraisal, farmers' group discussions and desk review were used for collecting data. Rice varieties Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…In Nepal, numerous studies have been performed on the effects of climate change on agriculture [8] [13] [22] [23] [24] [25], rice production [15] [16] [26] and climate change adaptation [24] [27] [28] [29] [30] [31]. Despite the interest in climate change adaptations at the local and regional levels, little literature is available on issues such as determinants, perceptions and barriers that affect the adoption of climate change adaptation options for rice production.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, numerous studies have been performed on the effects of climate change on agriculture [8] [13] [22] [23] [24] [25], rice production [15] [16] [26] and climate change adaptation [24] [27] [28] [29] [30] [31]. Despite the interest in climate change adaptations at the local and regional levels, little literature is available on issues such as determinants, perceptions and barriers that affect the adoption of climate change adaptation options for rice production.…”
Section: Introductionmentioning
confidence: 99%
“…Variation of extreme weather pattern rise in temperature,varied precipitation resulted declining production of crop in major region of Asia (Tragolraam et al 2011). Despite of rapid advancement in agriculture sector, weather is still key factor impacting crop productivity and declining yield (Sapkota, et al, 2010). Last 32 years of climatic data of Nepal showed that temperature has been increased by 1.8°C with average rise of 0.06°C per year along with high intensities of rainfall and less number of rainy days (Malla, 2009) where as computer simulation indicate that average global temperature will rise by 1.1-6.4°C by end of the 21 st century.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most important cereal crops of Nepalese agriculture and economy. It is grown in all agro-ecological zones from Terai plains (59 m at Musaharnia of Dhanusa district) to high hills up to 3050 masl (Chhumchure in Jumla district) including valleys and foot hills of Nepal (NARC, 2007;Sapkota et al, 2010). It is grown in about 1.48 million ha with the production of 5.04 Mahato and B.B.…”
Section: Introductionmentioning
confidence: 99%